THE CHANGES AND SPREAD OF SETTLEMENTS OF CHINESE PADANG, INDONESIA - Erniwati Erniwati; Arie Yulfa; Yelda Syafrina; Zulfa Saumia; Hendra Naldi; Surtani Surtani; Khairul Nizam (Indonesian Journal of Geography, 2023)
This article discusses the changes and distribution of Chinese settlements in Padang before and after 1945. This article aims to explain the process of change and distribution of Chinese settlements and identify the underlying factors. This article uses a historical approach by utilizing document and oral data by conducting FGDs. A field survey was conducted with a high-resolution satellite and processed with Geographical Information System (GIS). This article concludes; (1) During Dutch East Indies Government, the Chinese did not strictly isolated,  their settlement was found outside of the Chinese camp; (2) The distribution of Chinese settlements became more intense through expansion of the city and the development of settlements since the 1980s. (3) The 2009 Padang earthquake had a significant impact on the changes and distribution of Chinese settlements; (4) Currently, Chinese settlements are scattered in almost all city areas in form of lot and cluster housing with various types.